The effects of real and simulated microgravity on cellular mitochondrial function - Hong Phuong Nguyen; Phuong Hoa Tran; Kyu-Sung Kim; Su-Geun Yang (npj Microgravity, 2021)
Abstract Astronauts returning from space shuttle missions or the International Space Station have been diagnosed with various health problems such as bone demineralization, muscle atrophy, cardiovascular deconditioning, and vestibular and sensory imbalance including visual acuity, altered metabolic and nutritional status, and immune system dysregulation. These health issues are associated with oxidative stress caused by a microgravity environment. Mitochondria are a source of reactive oxygen species (ROS). However, the molecular mechanisms through which mitochondria produce ROS in a microgravity environment remain unclear. Therefore, this review aimed to explore the mechanism through which microgravity induces oxidative damage in mitochondria by evaluating the expression of genes and proteins, as well as relevant metabolic pathways. In general, microgravity-induced ROS reduce mitochondrial volume by mainly affecting the efficiency of the respiratory chain and metabolic pathways. The impaired respiratory chain is thought to generate ROS through premature electron leakage in the electron transport chain. The imbalance between ROS production and antioxidant defense in mitochondria is the main cause of mitochondrial stress and damage, which leads to mitochondrial dysfunction. Moreover, we discuss the effects of antioxidants against oxidative stress caused by the microgravity environment space microgravity in together with simulated microgravity (i.e., spaceflight or ground-based spaceflight analogs: parabolic flight, centrifugal force, drop towers, etc.). Further studies should be taken to explore the effects of microgravity on mitochondrial stress-related diseases, especially for the development of new therapeutic drugs that can help increase the health of astronauts on long space missions.